Efeitos do resveratrol isolado e/ou combinado ao ranelato de estrôncio no tecido ósseo de ratas ooforectomizadas e o perfil genotóxico destes tratamentos - Beirão, Dhyôvanna Carine Cardoso [UNIFESP] (2016)
To evaluate the effects of resveratrol (RSV) applied alone or combined (SrR+RSV) with strontium ranelate (SrR) on bone tissue constituents of ovariectomized rats and genotoxic profile of these treatments. Methods: 32 female Wistar rats, 6 months-old, were ovarietomized (OVX) and 8 were sham-operated (Sham). After 3 months, the animals were divided into five groups: Sham: received vehicle solution; Control: OVX and received vehicle solution; SrR: OVX and treated with 625mg/kg/day SrR; RSV: OVX and treated with 80mg/kg/day RSV; SrR+RSV: OVX and treated with 625mg/kg/day SrR + 80mg/kg/day RSV. The treatments and vehicle solution (H2O) were administered by gavage, 7 days/week during 90 days. The animals were weighed and submitted to bone densitometry at the ovariectomy day, beginning and end of treatment. After treatments, the animals were euthanized, and their distal femurs were fixed in 4% formaldehyde (derived from paraformaldehyde) in 0.1M phosphate buffer (pH 7.2), decalcified in EDTA 10% in a sodium phosphate buffer (pH 7.2), dehydrated in ethanol, diaphanized in xylene, impregnated and embedded in paraffin. The serial sections were performed with 5?m, adhered to slides for histomorphometry, histochemistry and immunohistochemistry analysis. The distal femurs were subjected to quantification of sulfated glycosaminoglycans by agarose gel electrophoresis and hyaluronic acid by ELISA. The biophysical and biomechanical properties were evaluated in tibiae and vertebrae. The analysis of cyto-genotoxicity was performed by Allium cepa test. Forty bulbs were divided into 8 groups: Control: vehicle solution; SrR10: 10?M SrR; SrR200: 200?M SrR; SrR1000: 1000?M SrR; RSV10: 10?M RSV; RSV25: 25?M RSV; RSV80: 80?M RSV; SrR200+RSV80: 200?M SrR + 80?M RSV. The meristems were collected after 48 hours of treatment for the analysis of root cells. Results: Body weight increased in all groups after OVX. At the end of treatment the fat percentage increased in SrR+RSV and lean mass decreased in SrR, RSV and SrR+RSV groups. All treatments were effective in increasing bone mineral density (BMD), but comparing the groups at the end of treatment, this increase was more evident in SrR+RSV group. The groups submitted to SrR treatment (isolated and/or combined) showed an increase in cancellous bone volume, indicating these treatments were more effective than resveratrol isolated. There was no difference in the thickness of cortical bone. The groups that received RSV (alone and/or combined) exhibited a predominance of thin fibers (immature fibers), while Sham, Control and SrR predominance, thick fibers (mature). All treatments decreased osteocytes death and increased osteoclasts, mainly in SrR group. The concentration of chondroitin sulfate decreased in Sham, SrR and SrR+RSV, while HA levels increased in Sham and SrR groups. There were no difference in calcium content and biophysical parameters of tibiae and vertebrae. Treatments with SrR applied alone exhibited cytotoxicity and genotoxicity, with clastogenic and aneugenic effects. While RSV (25?M and 80?M) and combined treatment were not cytotoxic, being able to reduce DNA damage, showing the anti-genotoxic potential of this phytoestrogen. Conclusion: Resveratrol applied alone and/or combined with strontium ranelate have different effects on bone tissue constituents. SrR demonstrates better efficacy in reestablishing bone microarchitecture, possibly by accelerating the remodeling process. RSV associated to SrR is more effective than isolated and protects the genotoxicity caused by SrR.